ANALISIS PEMASARAN GULA MERAH DI DESA SEPARE KECAMATAN LOANO KABUPATEN PURWOREJO - Fatmawati, Nurlaila; Indriyani, Damsi Rofiqoh (Jurnal Agroteknologi (Agronu), 2022)
Separe Village, Loano District, Purworejo Regency was chosen as a research site to analyze the marketing of brown sugar craftsmen. This study aims to determine the institutions involved and the marketing channels, marketing margins, farmer's share, and the ratio of profits and costs. The results showed that there are 2 types of brown sugar marketing channels in Separe Village, Loano District, Purworejo Regency, namely marketing channel I including craftsmen, retailers, and consumers and marketing channel II including craftsmen, collectors, retailers, and consumers. Marketing channel I has a marketing margin of Rp. 758/kg, farmer's share is 94.77% and the profit and cost ratio is 24.27. Meanwhile, marketing channel II has a marketing margin of Rp. 1258/kg, farmer's share is 91.16% and the profit and cost ratio is 18.35. Both channels are classified as efficient, but the most efficient is marketing channel I. Keywords: farmer's share, marketing margin,, marketing channel, profit ratio